2021
DOI: 10.1021/acssuschemeng.1c05504
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Seawater Desalination Footprint by Integrating Bipolar-Membrane Electrodialysis in a Single-Pass Reverse Osmosis Scheme

Abstract: Reverse osmosis (RO) is currently the most costefficient method for seawater (SW) desalination; however, producing high-quality water with a low boron concentration typically requires a two-pass process, which increases the required area and chemical consumption. We propose a sustainable and economic pathway for boron removal in a single RO step, thus reducing the area footprint. At the same time, chemicals are produced onsite from the RO brine using bipolar membrane electrodialysis (BMED), thus reducing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This technology has garnered attention for its versatility. For instance, Chaudhury et al integrated BMED into a seawater desalination process for boron removal and chemical recovery . Monat et al demonstrated that BMED should be a viable approach for cost-efficient and sustainable phosphogypsum processing by converting Na 2 SO 4 to NaOH and H 2 SO 4 for reuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology has garnered attention for its versatility. For instance, Chaudhury et al integrated BMED into a seawater desalination process for boron removal and chemical recovery . Monat et al demonstrated that BMED should be a viable approach for cost-efficient and sustainable phosphogypsum processing by converting Na 2 SO 4 to NaOH and H 2 SO 4 for reuse.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Chaudhury et al integrated BMED into a seawater desalination process for boron removal and chemical recovery. 12 Monat et al 13 demonstrated that BMED should be a viable approach for cost-efficient and sustainable phosphogypsum processing by converting Na 2 SO 4 to NaOH and H 2 SO 4 for reuse. Nevertheless, the application of BMED for treating brackish wastewater, which typically falls within a conductivity range of 1−10 g/L, has received limited attention in research.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Selective transport of cations across cation exchange membranes (CEMs) is vital in multiple applications like desalination and energy production by electrodriven transport (ED), reverse electrodriven transport, electrodeionization, capacitive deionization, etc. , Transport selectivity (i.e., ability to preferentially transport one cation over another) between multi- and monovalent cations is a prerequisite in processes like water softening, , metal ion extraction, , NaCl production from seawater, , etc., whereas the preferential transport among the monovalent cations is utilized in the process like recovery of Cs + from nuclear waste. , Along with the cationic composition and membrane characteristics, operation parameters are also known to affect the cation transport in CEMs . Therefore, an empirical understanding of the transport phenomena under various working conditions is necessary to improve the process efficiency. , In this regard, the working current/voltage is a crucial parameter in electrodriven processes.…”
Section: Introductionmentioning
confidence: 99%